Effectiveness and safety of endotracheal tube cuffs filled with air versus filled with alkalinized lidocaine: a randomized clinical trial - Navarro, Lais Helena Camacho; Braz, José Reinaldo Cerqueira; Nakamura, Giane; Lima, Rodrigo Moreira e; Silva, Fredson de Paula e; Módolo, Norma Sueli Pinheiro (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: High intracuff pressure in endotracheal tubes (ETs) may cause tracheal lesions. The aim of this study was to evaluate the effectiveness and safety of endotracheal tube cuffs filled with air or with alkalinized lidocaine. DESIGN AND SETTING: This was a prospective clinical study at the Department of Anesthesio- logy, Faculdade de Medicina de Botucatu, Universidade Estadual Paulista. METHODS: Among 50 patients, ET cuff pressures were recorded before, 30, 60, 90 and 120 minutes after starting and upon ending nitrous oxide anesthesia. The patients were randomly allocated to two groups: Air, with ET cuff inflated with air to attain a cuff pressure of 20 cmH2O; and Lido, with ET cuff filled with 2% lidocaine plus 8.4% sodium bicarbonate to attain the same pressure. ET discomfort before tracheal extuba- tion, and sore throat, hoarseness and coughing incidence were studied at the time of discharge from the post-anesthesia care unit, and sore throat and hoarseness were studied 24 hours after anesthesia. RESULTS: Pressures in Lido cuffs were significantly lower than in Air cuffs (p < 0.05). Tracheal complaints were similar for the two groups, except for lower ET discomfort and sore throat incidence after 24 hours and lower systolic arte- rial pressure at the time of extubation in the Lido group (p < 0.05). CONCLUSION: ET cuffs filled with alkalinized lidocaine prevented the occurrence of high cuff pressures during N2O anesthesia and reduced ET discomfort and postoperative sore throat incidence. Thus, alkalinized lidocaine-filled ET cuffs seem to be safer than conventional air- filled ET cuffs.